Analisis Rasio Laporan Keuangan pada PT Angkasa Pura I & II (Persero) Sebelum dan Saat Pandemi Covid-19 Periode 2018-2020 - Erlinda Octriwati Ritonga (Jurnal Multidisiplin Madani, 2022)
This study was to find out how the financial condition of PT Angkasa Pura I&II (Persero) before and during the Covid-19 pandemic based on calculations using the Liquidity Ratio (Current Ratio), Solvency (Debt to Assets Ratio), Profitability (Net Profit Margin) and Activity (Total Assets Turn Over). The data source used is secondary data obtained from the websites https://ap1.co.id/id and www.angkasapura2.co.id. The results of this study a comparison between the two companies through the calculation of the ratio. So it can be concluded that the two companies experienced a lot of decline in profit during the pandemic, but in terms of liquidity both companies were in poor numbers, namely in the 2020 period. This decline was largely due to the Large-Scale Social Restriction regulation which resulted in the temporary closure of several flight routes.